Technology Entrepreneurship Project (ENT 600) : 3 In 1 Multipurpose Shoes / Aiman Haakim Nor Azhar - Nor Azhar, Aiman Haakim; Mazzelan, Muhammad Aliffudin; Azizan, Muhammad Adam Ikhwan; Mohd Tahir, Muhammad Nussair; Abdul Wahab, Muhammad Aizzudin (2021)
This is an attempt to understand how the ideas may be implemented in a practical setting. As a student at UITM Perlis, everyone is required to complete a new product development project as part of their studies. So, for this aim, we were given the opportunity to design and innovate a product that is both deeply interesting to us and, of course, sports related, which is 3 In 1 Multipurpose Sport Shoes. In the first section, there was an overview to the new product development. In this section described the company background, objectives, difficulty that users experience while playing sports or participated in sports tournament, the methodological analysis, and the limitations. Next, the definition, categorization, and method of new product development were clearly detailed in the next portion of the study. The categorization of the new product is described by its enhancement and revisions. Furthermore, the process of developing a new product may be divided into five stages which are research and development, product design and features, idea testing, prototype, and test marketing. In the research and development phase, we talked about concept screening and concept generating. Furthermore, the idea testing and market survey testing were constructed in the form of questionnaires, which were delivered to 30 potential respondents using Google Form. Lastly, a few approaches were utilised in the test marketing to make this product acceptable to consumers, such as customers’ experience, thoughts, and comments on our new product. In conclusion, the input gathered from respondents was quite beneficial in assisting us in meeting the needs of consumers